Deer Exclusion Regenerates Native Plant Functional Responses, but Not Species Richness in an Eastern Serpentine Savannah - Richins, Allyson E.; Hulshof, Catherine M. (Frontiers in Conservation Science, 2022)
Plants are particularly vulnerable to physical disturbance in low productivity areas, due to the high energetic cost of replacing lost tissue. In the eastern United States, serpentine savannahs are fragmented ecosystems with high concentrations of rare endemic plant species, low concentrations of soil nutrients, and severe deer overpopulation. This study assessed the recovery of flowering plants in a serpentine savannah when deer were excluded. Plant count, flower count, vegetative area, and plant height of 10 serpentine plant species were compared inside and outside of deer exclusion structures throughout an entire growing season. Throughout the growing season and across the plant community, deer exclusion consistently increased values for all plant response traits measured. Species that responded most strongly to deer exclusion included Arabis lyrata (Brassicaceae, the wide ranging lyre-leaf rockcress) and the serpentine near-endemic Symphyotrichum depauperatum (a serpentine aster known only in the eastern US). The slender knotweed, Polygonum tenue performed worse in excluded areas, which may indicate exclusion by more competitive species, or, alternatively, local scarcity. Overall, species richness did not increase in excluded plots, which may indicate that years of deer overbrowsing have depleted the local seed banks. We recommend that further restoration efforts should include reintroductions of locally extirpated species, in combination with deer exclusion to allow rare serpentine plant communities and their seedbanks to recover from intense overbrowsing pressure.